Pengaruh Model Pembelajaran Kontekstual pada Media Monopoli terhadap Hasil Belajar Siswa IPS Kelas 4 SD dalam Mengenalkan Negara di Dunia - Al Amin; Sutrisno Sutrisno (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to determine the effect of contextual learning models on monopoly media on the learning outcomes of 4th grade elementary school social studies students in introducing countries in the world. The use of contextual learning models using monopoly media can improve students' social studies learning outcomes, because students gain knowledge by developing and finding their own thought patterns. Through this contextual learning approach, real activities are prioritized so that students can find concepts in learning materials and connect these concepts to students' real-world lives. The research method used is a qualitative research and development method. This research method was chosen to produce certain products and test the effectiveness of these products. Based on the results of the study and discussion, it can be concluded that the use of contextual learning models using monopoly media can improve students' social studies learning outcomes IV. In monopoly media, critical thinking skills are trained in recognizing various countries in the world. These results indicate that there is a difference in the effect of implementing monopoly media and simply explaining by the teacher on students' learning outcomes. The results of the study can be concluded that the use of appropriate learning media by paying attention to the material and objectives to be achieved in the learning process.